Performance and carcass characteristics of growing rabbits as affected by the dietary inclusion of a natural zeolite - FORTOMARIS (Π. ΦΟΡΤΟΜΑΡΗΣ), P.; ARSENOS (Γ. ΑΡΣΕΝΟΣ), G.; CHRISTAKI (Ε. ΧΡΗΣΤΑΚΗ), E.; FLOROU-PANERI (Π. ΦΛΩΡΟΥ - ΠΑΝΕΡΗ), P. (Journal of the Hellenic Veterinary Medical Society, 2017)
The objective of this study was to assess the effect of a diet containing a clinoptilolite rich material (tuff) on growth and carcass characteristics of fattening rabbits. Three diets were formulated; diet C was a standard commercial diet that served as control, while diet L contained 1.25% natural zeolite (NZ) and diet Η contained 2.5% NZ. Seventy-two New Zealand χ Californian rabbits were used after weaning at 35 days of age. They were randomly allocated into three groups (n=24, with three replicates of four male and four female rabbits each, balanced for body weight) according to the above dietary treatments. All rabbits were weighed individually on weaning and thereafter on weekly basis. Feed intake was monitored weekly on subgroup basis. The experiment lasted 8 weeks. Performance traits and mortality level were recorded in the aforementioned period. In the end of this period all rabbits were stunned and slaughtered to obtain the European carcass weight. Six carcasses per group (two per subgroup, one male and one female) were randomly selected for the determination of carcass characteristics. The results of the current study showed that the incorporation of a clinoptilolite rich tuff (natural zeolite) in the diet of growing rabbits did not affect their growth or the carcass characteristics, whereas feed efficiency and mortality level were negatively affected.